Moran Brothers Company employee with drill at the shipyard on Western Avenue, Seattle, circa 1900 - Jacobs, Frank , 1881-1979
Robert Moran (1857-1943) and his brothers Frank and Sherman established Moran Bros. Marine and Sawmill Machinery Co. (later Moran Bros. Co.) in Seattle in 1882. In 1898, the firm built a fleet of 12 steamers and 10 barges, and delivered them on the Yukon River to carry food to the miners. The firm also built many large steel and wood vessels, including the U.S. battleship NEBRASKA. Moran served as mayor of Seattle from 1888 to 1890, and retired in 1906 to Orcas Island. In 1914, he donated 5,000 acres on Orcas Island to the State of Washington, which became Moran State Park. This image shows an employee of Moran Brothers Company posing with a drill at the shipyard on Charles Street in Seattle, circa 1900. A pioneer in the field of photojournalism, photographer Frank Jacobs (1881-1979) covered events big and small throughout the Pacific Northwest from 1907-1945. Although he spent most of his career with the Seattle Post-Intelligencer, he also had stints with other publications, ran his own photography studio, served as an early motion picture cameraman for the Pathe News, and had the opportunity to photograph eight Presidents. Handwritten under image: Drilling boiler plate Stamped on verso: Frank Jacobs, Photographer and Artist, Seattle Caption information source: ""Jacobs, Frank,"" Eric Flom, historylink.org Essay3258 1 photographic print: b&w; 8 x 10 in.